Postoperative Wound Infections and the Antimicrobial Susceptibility in Baghdad Hospitals - Maysoon A. Merdaw (College of Pharmacy University of Baghdad, 2017)
Nosocomial infections are one of the most important causes of mortality and morbidity in hospitals. These are major public health problems worldwide, but particularly in developing countries. The purpose of this research was to analyze the frequency of the microorganisms in the specimens taken from the surgical wounds, and to examine antimicrobial susceptibility for some isolates . Wound swabs were examined from June 2010 to January 2011. The isolates were identified by conventional methods, antimicrobial susceptibility testing was performed by Kirby-Bauer disc diffusion method as per NCCLS guidelines.A total of 102 wound swabs were examined 22(21.56%) swabs were sterile and 80(78.43%) were positive for microorganisms. The results showed 27.2% positive for Pseudomonas aeruginosa, 25.0% positive for Coagulase positive Staphylococci, 20.0% positive for Enterococcus spp., 17.5% positive for Escherichia coli,15.0% positive for Klebsiella pneumonia,13.7% for Proteus mirabilis,and10.0% for Acinetobacter baumannii. Antimicrobial susceptibility testing showed that the rate of isolates of Imipenem Resistance Pseudomonas aeruginosa(IRPA) were 3.7% , 11.2% positive for Vancomycin Resistance Enterococci(VRE) ,13.7% positive for both Methicillin Resistance Staphylococcus aureus(MRSA)and Vancomycin Resistance Staphylococcus aureus(VRSA) ,and 11.2% positive for Vancomycin Intermediate Staphylococcus aureus(VISA). We found that postoperative wound infections increase with pre and post operative hospitalization  that's mean the infections can be decrease by shortening the hospitalization time.Our results appear to be maintained with strategies for preventing nosocomial infection,permanent education, strong application of protocols and urging the implementation of strict infection control policy. Key words: nosocomial infection, surgical wound, antimicrobial susceptibility.